Soft Skills Requirements for Engineering Entrepreneurship - Jaimes-Acero, Yenny-Carolina; Granados-Comba, Adriana; Bolivar-León, Rafael (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Entrepreneurship is a vector that helps economic growth, social scaling, and job generation. However, the soft skills required for engineering entrepreneurship are unclear. This research aims to determine which of these skills are highly demanded as a reference to improve competitiveness among engineers and undergraduate programs. A survey was designed and applied to graduated mechanical engineers from the University of Pamplona. The instrument with excellent validity and reliability, according to Cronbach’s Alpha, included 4 different dimensions evaluating 10 soft skills with 18 indicators. The statistical tools used were the Kolmogorov-Smirnov test, median, mode, Kruskal-Wallis ANOVA, and the Games-Howell post hoc test. All soft skills investigated are required to start an engineering venture at a high development level. Likewise, the surveyed engineers demonstrated a high level of development of these skills in such a way that the gap between those required to start an engineering entrepreneurial venture and those developed is minor. In addition, the most effective way to increase its development is training in administrative areas or personal development. Likewise, there is a small gap between the skills developed by the respondents and those required in a venture, and the way to overcome this gap is training in administrative areas or personal development. Engineers dedicated to teaching, or working in public institutions, have less developed three of the six entrepreneurship indicators. Finally, the gap between soft skills developed in undergraduate programs and those required in entrepreneurship is significant. Engineering programs must include experiential training in soft skills and entrepreneurship in their curriculum.